Exploring transference in the translation of proper names in Ratih Kumala's Cigarette Girl - Juliartha, Komang Rama; Hikmaharyanti, Putu Desi Anggerina (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2024)
This study explores the use of the transference translation procedure in translating proper names in the novel Cigarette Girl by Ratih Kumala. It aims to determine the frequency of transference translation procedure usage in translating proper names and to investigate the reasons behind the translator's decision to retain certain names unmodified. Using a qualitative descriptive method, data were collected from the English and Indonesian versions of Cigarette Girl through observation and note-taking, then analyzed descriptively. The results indicate that the transference procedure was used a total of 62 times in translating proper names. The highest frequency of transference application was found in the categories of personal names and personifications, with a total of 30 instances. The lowest frequency was in the category of unique event names, with only one instance. The primary reason for using the transference procedure was to preserve the specific meanings embedded in the original names.